2020
DOI: 10.1016/j.ipm.2019.102080
|View full text |Cite
|
Sign up to set email alerts
|

Information needs of drug users on a local dark Web marketplace

Abstract: This study examines the nature of context-sensitive information needs by focusing on the articulations of need for disnormative information among drug users. To this end, the sample of 9300 messages posted to Sipulitori, a Finnish dark web site were examined by means of descriptive statistics and qualitative content analysis. The theoretical framework of the study was developed by drawing on Tom Wilson´s idea of information need as a phenomenon fundamentally triggered by physiological, affective and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
0
23
0
5
Order By: Relevance
“…Most significantly, the study found that drug use and trading dominated the information needs and information sharing of the users to a great extent (see also [23]). Questions and answers about other things (sex, work, money, hobbies) were made from a point of view in which drug use was taken as the established, shared baseline.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Most significantly, the study found that drug use and trading dominated the information needs and information sharing of the users to a great extent (see also [23]). Questions and answers about other things (sex, work, money, hobbies) were made from a point of view in which drug use was taken as the established, shared baseline.…”
Section: Discussionmentioning
confidence: 98%
“…Libertarian thinking, including agorism, in the style of the old Silk Road (see e.g., [21,27]) was present on Sipulitori, but very rare. The users were far more likely to discuss daily habits or lifecontrol problems than any ideological points about the liberty to trade in what one wants and to use any substance one wants [23]. Without interviews, it is not possible to be certain about the value systems of the site's users, but the absence of such talk on also lifestyle-related forum sections was rather conspicuous.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations